High-efficiency electrosynthesis of urea over bacterial cellulose regulated Pd–Cu bimetallic catalyst. Issue 1 (11th November 2022) - Zhang, Shengbo; Geng, Jing; Zhao, Zhong; Jin, Meng; Li, Wenyi; Ye, Yixing; Li, Ke; Wang, Guozhong; Zhang, Yunxia; Yin, Huajie; Zhang, Haimin; Zhao, Huijun
Abstract : PdCu/CBC exhibited a remarkable R urea of 763.8 ± 42.8 μg h −1 mgcat. −1 at −0.50 V ( vs. RHE) and an exceptional FE of 69.1 ± 3.8% at −0.40 V ( vs. RHE). Taking advantage of operando spectroscopy characterization, the C–N coupling mechanism was verified. Abstract : Ambient synthesis of urea through electrocatalytic coupling reaction of carbon dioxide (CO2 ) with nitrate (NO3 − ) has been regarded as a promising means to substitute the industrial energy- and capital-concentrated Haber–Bosch and Bosch–Meiser processes. Here we report the fabrication of PdCu alloying nanoparticles (NPs) anchored on carbonized bacterial cellulose (CBC) (PdCu/CBC) for ambient electrosynthesis of urea. As the electrocatalyst, the PdCu/CBC exhibits superior electrocatalytic activity toward urea synthesis with CO2 and NO3 −, affording a remarkable urea yield rate of 763.8 ± 42.8 μg h −1 mgcat. −1 at −0.50 V ( vs. RHE) and an exceptional faradaic efficiency (FE) of 69.1 ± 3.8% at −0.40 V ( vs. RHE) under ambient conditions. The theoretical calculations unveil that this alloying catalyst provides Pd and Cu dual active sites with favored internal electron transferability, enabling generation of key *NO2 and *CO2 intermediates to facilitate C–N coupling reaction for urea synthesis. The operando spectroscopy characterization studies support the theoretical calculation results. To ensure the accuracy of the analysis data in this work, we investigated in detail the influence of the by-products in urea synthesis on the diacetyl monoxime colorimetric method and 1 H nuclear magnetic resonance method for urea quantitative determination.